أثر التمكين على تنمية السلوك الإبداعي لدى العاملين – دراسة ميدانية للبنك الوطني الجزائري لولاية سوق أهراس - - يسرى حزايمية; حنان تلايلية (My University, 2022)
The study aimed to adopt the impact of empowerment on the development of creative behavior among workers, at the National Bank of Algeria - Agency of Souk Ahras (Algeria), and to achieve the objectives of the study, the researcher developed a questionnaire distributed on a simple random sample of 33 employees, and to achieve the objectives of the study the questionnaire was used to collect data, in the light of The data were collected and analyzed and hypotheses tested using the Statistical Package for Social Sciences (SPSS) program. Among the most important results that were reached:  There is a high interest in empowering the employees of the National Bank of Algeria under study.  There is a high interest in the creative behavior of workers in the Algerian National Bank under study.  There is a strong direct correlation between empowerment as an independent variable and the creative behavior of workers as a dependent variable in the National Bank of Algeria under study. .......................................... هدفت الدراسةإلى تبني أثر التمكين على تنمية السلوك الإبداعي لدى العاملين,بالبنك الوطني الجزائري _لوكالة سوق أهراس ) الجزائر(,ولتحقيق أهداف الدراسة ,قام الطالب بتطوير إستبانة موزعة على عينة عشوائية بسيطة مكونة من 33 موظف,ولتحقيق أهداف الدراسة تم إستخدام الإستبانة لجمع البيانات,في ضوء ذالك جرى جمع وتحليل البيانات وإختبار الفرضيات بإستخدام برنامج الحزم الإحصائية للعلوم الإجتماعية ) spss ( وكان من بين أهم النتائج التي تم التوصل إليها:  هناك إهتمام مرتفع لتمكين العاملين بالبنك الوطني الجزائري محل الدراسة .  هناك إهتمام عال للسلوك الإبداعي للعامليم بالبنك الوطني الجزائري محل الدراسة.  توجد علاقة إرتباطية طردية قوية بين التمكين كمتغير مستقل والسلوك الإبداعي لدى العاملين كمتغير تابع بالبنك الوطني الجزائري محل الدراسة .